Treatment, Survival, and Prognosis of Advanced-Stage Natural Killer/T-Cell Lymphoma: An Analysis From the China Lymphoma Collaborative Group - Liu, Weiping; Yang, Yong; Qi, Shunan; Wang, Ying; He, Xia; Zhang, Liling; Qu, Baolin; Qian, Liting; Hou, Xiaorong; Qiao, Xueying; Wang, Hua; Li, Gaofeng; et al. (Frontiers in Oncology, 2021)
Patients with advanced-stage natural killer/T-cell lymphoma (NKTCL) usually have a poor prognosis. However, there is limited data of comprehensive analysis on this particular patient population due to the rarity of the disease. The present study aimed to investigate the treatment models, survival outcomes, and prognosis of advanced-stage NKTCL. Data from 336 patients with advanced-stage NKTCL diagnosed between 2006 and 2015 in the China Lymphoma Collaborative Group database were retrospectively analyzed. The median age was 42 years and the male/female ratio was 2.4:1. About 97% of patients had stage IV disease and 77% had > 1 extranodal involvement site. All patients received chemotherapy, with the most common option being asparaginase (Asp)-containing regimens (n=146; 43.5%). Among 286 patients with available response data, the overall response rate (ORR) was 57.3% with a complete remission (CR) rate of 35.7%. Asp-containing regimens led to better ORRs (86/132, 65.2% vs. 54/113, 47.8%, P=0.006) and CR rates (60/132, 45.5% vs. 27/113, 23.9%, P<0.001) than non-Asp-containing regimens. The expected 5-year progression-free survival (PFS) and overall survival (OS) rates were 22.6% and 32.0%, respectively, for the whole cohort. Compared to non-Asp-containing chemotherapy, Asp-containing chemotherapy improved 5-year PFS (34.2% vs. 17.1%, P<0.001) and OS (45.3% vs. 27.8%, P<0.001). A trend towards improvement in OS was observed when gemcitabine was added to Asp-containing chemotherapies. Moreover, those undergoing autologous hematopoietic stem cell transplantation had prolonged survival time. In conclusion, Asp-containing chemotherapy could improve the prognosis of advanced-stage NKTCL, and refinement of treatment models is warranted in the future.